Utopia and Ekphrasis: Italo Calvino’s View - Pocci, Luca (Quaderni d'Italianistica)

(untitled) (Iter Press, 2022)
This essay sets itself two objectives. The first objective is to call attention to how Calvino looks at the visual style of Charles Fourier’s writings as a model of utopianism that aspires to achieve a maximum degree of ekphrastic effect and vision. To this model, as it is shown, Calvino opposes a perspective consisting of envisioning utopia not in the form of fullness and plenitude (the fullness and plenitude of a perspicuous and complete picture) but in the form of glimpses and fragments. The second objective is to bring into focus the restrained ekphrastic force of Calvino’s utopia that emerges, most prominently in Le città invisibili. As it is argued, this restrained ekphrasis generates a utopianism without utopia, the author’s response to the crisis of contemporary utopian imagination.